2016
DOI: 10.1021/acs.jmedchem.6b00473
|View full text |Cite
|
Sign up to set email alerts
|

Underexplored Opportunities for Natural Products in Drug Discovery

Abstract: The importance of natural products in the treatment of human disease is well documented. While natural products continue to have a profound impact on human health, chemists have succeeded in generating semisynthetic analogues that sometimes overshadow the original natural product in terms of clinical significance. Synthetic efforts based on natural products have primarily focused on improving their drug-like features while targeting utility in the same biological space. A less documented phenomenon is that nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 105 publications
0
59
0
1
Order By: Relevance
“…13 Recent studies have suggested that Food and Drug Administration (FDA)-approved or clinically investigational natural products often target multiple proteins, called polypharmacology. 4 However, polypharmacology of natural products are characterized with both therapeutic effects and unwanted adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…13 Recent studies have suggested that Food and Drug Administration (FDA)-approved or clinically investigational natural products often target multiple proteins, called polypharmacology. 4 However, polypharmacology of natural products are characterized with both therapeutic effects and unwanted adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several plant-derived drugs are in use today, including, for example, vinblastine (from Catharanthus roseus (L.) G. Don, used to treat childhood leukemia); paclitaxel (from Taxus brevifolia Nutt., used to treat ovarian cancer); morphine (from Papaver somniferum L., used to treat pain); and quinine (from Cinchona spp., used to treat malaria) [5]. Not only are phytochemicals useful medicines in their own right, but compounds derived from them or inspired by them have become useful medicines [6,7]. For example, Artemisia annua L., a plant originally used in Traditional Chinese Medicine to treat fever, is the source of artemisinin, a clinically-useful antimalarial sesquiterpenoid [8]; the antihypertensive drug reserpine, isolated from the roots of Rauvolfia serpentina (L.) Benth.…”
Section: Introductionmentioning
confidence: 99%
“…These include multiple classes of antibacterials, as well as oncology drugs, diabetes drugs, hypocholesterolemic drugs, and immunomodulatory agents 1,2 . The global rise in antibiotic resistance 3,4 , the increased promise of immunomodulatory agents in cancer treatment 5 , and the continued need for development of new drugs across novel and complex biology is contingent upon the identification of structurally diverse bioactive compounds [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%